2020
DOI: 10.1093/mnras/staa409
|View full text |Cite
|
Sign up to set email alerts
|

NGC 7469 as seen by MEGARA: new results from high-resolution IFU spectroscopy

Abstract: We present our analysis of high-resolution (R ∼ 20 000) GTC/MEGARA integral-field unit spectroscopic observations, obtained during the commissioning run, in the inner region (12.5 arcsec × 11.3 arcsec) of the active galaxy NGC 7469, at spatial scales of 0.62 arcsec. We explore the kinematics, dynamics, ionisation mechanisms and oxygen abundances of the ionised gas, by modelling the Hα-[N II] emission lines at high signal-to-noise (> 15) with multiple Gaussian components. MEGARA observations reveal, for the fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 99 publications
(140 reference statements)
0
22
0
Order By: Relevance
“…In ESO 320-G030, a nuclear disk with projected radius of ≈ 40 pc attains these conditions, though still with moderately warm dust (T dust ≈ 55 K). The disk is distorted, elongated in the direction of the bar, and highly turbulent (∆V/V rot ≈ 1); it is thus expected to be geometrically thick (e.g., Cazzoli et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In ESO 320-G030, a nuclear disk with projected radius of ≈ 40 pc attains these conditions, though still with moderately warm dust (T dust ≈ 55 K). The disk is distorted, elongated in the direction of the bar, and highly turbulent (∆V/V rot ≈ 1); it is thus expected to be geometrically thick (e.g., Cazzoli et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rupke & Veilleux 2013;Cazzoli et al 2014Cazzoli et al , 2016Pereira-Santaella et al 2016Fluetsch et al 2021) and luminous AGNs (e.g. quasars or Seyferts galaxies; Feruglio et al 2010;Müller-Sánchez et al 2011;Fiore et al 2017;Brusa et al 2018;Venturi et al 2018;Cazzoli et al 2020). These works demonstrated the power of the 3D IFS in studies of this kind.…”
Section: Introductionmentioning
confidence: 76%
“…Language 3 (IDL) environment for the [N ii] λ6584 Å and [S ii] emission lines separately (e.g., Cazzoli et al 2020). We found that constraints to the line widths of FWHM < 1 Å (≈ 45 km s −1 at the rest-frame wavelengths of these lines) and absolute radial velocities with respect to the systemic velocity 4 (|v r |) between 130 and 250 km s −1 produced optimal results.…”
Section: Data Analysis: Mapping the Jetmentioning
confidence: 85%